2019
DOI: 10.1158/1078-0432.ccr-18-1033
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and Glucocorticoid-induced Kinase Sgk1 Directly Promotes the Differentiation of Colorectal Cancer Cells and Restrains Metastasis

Abstract: Background and Aims The molecular events that determine intestinal cell differentiation are poorly understood and it is unclear whether it is primarily a passive event or an active process. It is clinically important to gain a greater understanding of the process, since in colorectal cancer (CRC), the degree of differentiation of a tumour is associated with patient survival. SGK1 has previously been identified as a gene that is principally expressed in differentiated intestinal cells. In colorectal cancer (CRC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…The results of the present study illustrated that low Sgk1 expression in EAC tumor cells was associated with adverse clinical outcomes. The result was in line with previous findings that showed that low Sgk1 activation predicted poor prognosis of colon cancer patients 19 . The possible mechanism was proposed to be decreased cellular dedifferentiation and migration via PIPK3 expression, which could regulate inflammatory response 19 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present study illustrated that low Sgk1 expression in EAC tumor cells was associated with adverse clinical outcomes. The result was in line with previous findings that showed that low Sgk1 activation predicted poor prognosis of colon cancer patients 19 . The possible mechanism was proposed to be decreased cellular dedifferentiation and migration via PIPK3 expression, which could regulate inflammatory response 19 …”
Section: Discussionsupporting
confidence: 91%
“…GR downregulation in epithelial cells induces the expression of various proinflammatory genes, including those encoding cytokines and adhesion molecules 12 . It has also been reported that activation of GR and Sgk1 in carcinoma cells inhibits the expression of various proinflammatory genes and suppresses cancer progression 17‐19 . In vitro and in vivo studies have shown that GR activation in urinary bladder carcinoma cells suppresses tumor invasion and metastasis by decreasing cell migration and invasion via matrix metalloproteinase (MMP)‐2/MMP‐9 and interleukin (IL)‐6 downregulation 17 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Waldegger et al, 1997;Lee et al, 2012;Lang and Stournaras, 2013;Lang et al, 2018 Signaling of SGK1 activation PI-3 kinase-sensitive 3-phosphoinositide (PIP3)-dependent kinases PDK1 and PDK2, Na + /H + exchanger regulating factor 2 (NHERF2), WNK1 (lysine deficient protein kinase 1), mammalian target of rapamycin mTOR complex-2 (mTORC2) composed of mTOR, Rictor (rapamycin-insensitive companion of mTOR), Sin1 (stress-activated protein kinase-interacting protein 1), mLST8 and Protor-1, p38α MAPK, ERK5, cAMP, Ca 2+ -sensitive calmodulin-dependent protein kinase kinase (CaMKK), G-protein Rac1 Waldegger et al, 1997;Lang et al, 2006;Dibble et al, 2009;Peterson et al, 2009;Rosner et al, 2009;Heise et al, 2010;Lyo et al, 2010;Treins et al, 2010;Pearce et al, 2011;Fang et al, 2012;Hall et al, 2012;Na et al, 2013;Thomanetz et al, 2013;Domhan et al, 2014;Tsai et al, 2014;Lang et al, 2018. Heise et al, 2010;Schmidt et al, 2014;Lee et al, 2019). In agreement, SGK1 overexpression can confer resistance of cancer cells to chemotherapy and radiation (Sommer et al, 2013;Talarico et al, 2016).…”
Section: Regulators Example Referencesmentioning
confidence: 99%
“… 1 , 3 , 14 , 15 SGK1 has been previously reported in hypertension, diabetes, hypercoagulability, and autoimmune disease. 5 , 16 , 17 A growing number of recent studies reveal a role for SGK1 in human tumors such as glioblastoma, 18 20 breast, 21 25 colorectal, 26 28 prostate, 29 31 thyroid, 32 ovarian, 33 myeloma, 11 and non-small cell lung cancer 34 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%